2016
DOI: 10.1002/app.43804
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, catalytic and splinting activity of nano Ag end capped l‐glutathione bridged amphiphilic diblock copolymer

Abstract: l‐glutathione, a naturally occurring environmental friendly amino acid, was used as an initiator towards the ring opening polymerization (ROP) of ɛ‐caprolactone (CL) followed by the ROP of tetrahydrofuran (THF). The thiol group of l‐glutathione reduces Ag+ ions and chemically bound to the surface of Ag nanoparticles. The ROP of CL was carried out at 160 °C under nitrogen atmosphere in the presence of stannous octoate(SO) as catalyst whereas the ROP of THF was carried out at 45 °C for 24 h in the presence of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 43 publications
(80 reference statements)
2
26
0
Order By: Relevance
“…ions. Thus, the appearance of new peaks and shifting in the peak position (Jeyapriya et al 2016) confirmed the Nickel complex formation with AC.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…ions. Thus, the appearance of new peaks and shifting in the peak position (Jeyapriya et al 2016) confirmed the Nickel complex formation with AC.…”
Section: Resultsmentioning
confidence: 59%
“…Figure 1a indicates the FTIR spectrum of AC. A broad peak around 3432 cm -1 is due to O-H stretching (Jeyapriya et al 2016). A twin peak at 2937 and 3048 cm -1 are corresponding to the free -NH 2 stretching.…”
Section: Resultsmentioning
confidence: 97%
“…The PCL was prepared by ROP of CL through bulk polymerization method. The standard procedure in brief is mentioned below: In a 25‐mL capacity round bottomed flask (RBF), 2‐g CL monomer is taken. 0.001‐g catalyst, S.O was added into the RBF.…”
Section: Methodsmentioning
confidence: 99%
“…Thus prepared nano Ag doped diblock copolymer was tested for its catalytic activity. For this purpose, reduction of NiP was considered . 6.7 × 10 −3 g NiP was accurately weighed and dissolved in 50‐mL DD water.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, polymer‐supported catalyst systems have been used to prevent decreases in the concentration of catalyst and to control the reaction. For example, a silver nanoparticle end capped diblock copolymer was used for the reduction of NiP . Similarly, other systems, such as diblock copolymer–V 2 O 5 , fluorescent polyimide–V 2 O 5 nanocomposite, chitosan Schiff base–V 2 O 5 , poly(epichlorohydrin‐ g ‐acid fuchsin)–hydroxyapatite, poly (caprolactone‐ co ‐morpholine)–silver, poly(lactide)–palldium, poly(urethane)–gold, polyhydroxyalkonate–silver, poly(dimethyl aminoethyl methacrylate)–grapheneoxide, chitosan–iron, and polyacrylamide–gold systems, have been used for the catalytic reduction of NiP.…”
Section: Introductionmentioning
confidence: 99%